Deep Venous Arterialization: Background, Patient Selection, Technique, Outcomes and Follow-up, and Future Implementation - Zaman, Naveed; Rundback, John (Seminars in Interventional Radiology, 2023)
Critical limb-threatening ischemia (CLTI) is a severe manifestation of peripheral arterial disease with a highly increased risk for morbidity and mortality that has limited and suboptimal opportunities for treatment, ultimately resulting in major amputation for patients. Deep venous arterialization (DVA) provides a suitable limb salvage option for “no-option” patients facing amputation by introducing an artificial anastomosis between a site of proximal arterial inflow and retrograde venous outflow to deliver tissue perfusion to lower extremity wounds. Because DVAs are employed as a last-resort effort in CLTI patients, it is important to provide updated information on indications for usage, strategies in creating DVA conduits, and discussion of outcomes and expectations for patients undergoing this procedure. Additionally, variations in method, including use of various techniques and devices, are explored. The authors provide an up-to-date review of the literature and discuss pertinent procedural and technical considerations for utilizing DVAs in CLTI patients.
Keywords: deep venous arterialization; chronic limb-threatening ischemia; peripheral arterial disease; endovascular therapy; interventional radiology